Hierarchical Graphene Foam for Efficient Omnidirectional Solar–Thermal Energy Conversion. Issue 38 (18th August 2017) - Ren, Huaying; Tang, Miao; Guan, Baolu; Wang, Kexin; Yang, Jiawei; Wang, Feifan; Wang, Mingzhan; Shan, Jingyuan; Chen, Zhaolong; Wei, Di; Peng, Hailin; Liu, Zhongfan
Abstract : Efficient solar–thermal energy conversion is essential for the harvesting and transformation of abundant solar energy, leading to the exploration and design of efficient solar–thermal materials. Carbon‐based materials, especially graphene, have the advantages of broadband absorption and excellent photothermal properties, and hold promise for solar–thermal energy conversion. However, to date, graphene‐based solar–thermal materials with superior omnidirectional light harvesting performances remain elusive. Herein, hierarchical graphene foam (h‐G foam) with continuous porosity grown via plasma‐enhanced chemical vapor deposition is reported, showing dramatic enhancement of broadband and omnidirectional absorption of sunlight, which thereby can enable a considerable elevation of temperature. Used as a heating material, the external solar–thermal energy conversion efficiency of the h‐G foam impressively reaches up to ≈93.4%, and the solar–vapor conversion efficiency exceeds 90% for seawater desalination with high endurance. Abstract : A hierarchical graphene foam (h‐G foam) with continuous porosity is designed and grown by plasma‐enhanced chemical vapor deposition. This foam shows dramatic enhancement of broadband and omnidirectional absorption of sunlight, with an external solar–thermal energy conversion efficiency of ≈93.4%. The solar–vapor conversion efficiency exceeds 90% for seawater desalination.